Dietary practices of men in Bangladesh: Evidence from the National Nutrition Surveillance - Mridha, Malay; Shamim, Abu Ahmed; Hossain, Md. Mokbul; Hasan, Mehedi; Hanif, Abu Abdullah Mohammad; Hossaine, Moyazzam; Ullah, Mohammad Aman; Sarker, Samir Kanti; Rahman, S. M. Mustafizur; Mitra, Dipak Kumar; Haque, Md. Emdadul (Oxford Academic, 2022)
This article was published in Current Developments in Nutrition by Oxford Academic [Oxford University Press Copyright © Oxford University Press 2020.] and the definite version is available at: https://doi.org/10.1093/cdn/nzaa046_049 The Journal's website is at: https://academic.oup.com/cdn/article/4/Supplement_2/549/5845844